Ludic Ubuntu ethics - Nagel, Mechthild, author.
1 online resource (xix, 221 pages)
Keywords: "Rethinking Indigenous Justice: Ludic Ubuntu Ethics? develops a positive peace vision, taking a bold look at African and Indigenous justice practices and proposes new relational justice models. 'Ubuntu' signifies shared humanity, presenting us a sociocentric perspective of life that is immensely helpful in rethinking the relation of offender and victim. In this book, Nagel introduces a new theoretical liberation model - ludic Ubuntu ethics - to showcase five different justice conceptions through a psychosocial lens, allowing for a contrasting analysis of negative Ubuntu (eg., through shaming and separation) towards positive Ubuntu (eg., mediation, healing circles, and practices that no longer rely on punishment). Providing a novel perspective on penal abolitionism, the volume draws on precolonial (pre-carceral) Indigenous justice perspectives and Black feminism, using discourse analysis and a constructivist approach to justice theory. Nagel also introduces readers to a post secular turn by taking seriously the spiritual dimensions of healing from harm and highlighting the community's response. Spanning disciplinary boundaries and aimed at readers seeking to understand how to move beyond reintegrative shaming and restorative justice theories, the volume will engage scholars of criminology, philosophy and law, and more specifically penal abolitionism, social ethics, peace studies, African studies, critical legal studies, and human rights. It will also be of great interest to practitioners and activists in restorative justice, mediation, social work, and performance studies"--